Microstructure study on functionally graded HAP-F75 fabricated by powder metallurgy - Noorazimah, A. (SIRIM, 2011)
4th Malaysian Powder Metallurgy Symposium (MPMS) and Malaysian Metallurgical Conference (MMC) 2010 organized by SIRIM Berhad on 22nd - 23rd November 2010 at Parkroyal Hotel, Penang, Malaysia.